2020
DOI: 10.1186/s13007-020-00618-0
|View full text |Cite
|
Sign up to set email alerts
|

A cell suspension based uptake method to study high affinity glucosinolate transporters

Abstract: Background: Glucosinolates are an important class of secondary metabolites characteristic to the order Brassicales. They are known to play a major role in plant defense and from the human perspective, can be anticarcinogenic or antinutritive. GTRs are plasma-membrane localized high affinity glucosinolate transporters, which are important components of the source (leaf) to sink (seed) translocation of intact glucosinolates in members of Brassicaceae family. GTRs are identified as major candidates for Brassica c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…In order to characterize multiple GTR s identified in Brassica species, we utilized a novel plant‐based transport assay system generated from non‐embryogenic calli of cotton cotyledons (CCL‐1), that can be maintained as homogenous cell suspension cultures (Nambiar et al, 2020; Singh & Pental, 2015). We decided to investigate any possible differences in specificity for different glucosinolate substrates among the GTR1 and GTR2 homologs of “A” subgenome, which constitutes half of the genome of two globally important oilseed crops, B. juncea (AABB) and B. napus (AACC).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In order to characterize multiple GTR s identified in Brassica species, we utilized a novel plant‐based transport assay system generated from non‐embryogenic calli of cotton cotyledons (CCL‐1), that can be maintained as homogenous cell suspension cultures (Nambiar et al, 2020; Singh & Pental, 2015). We decided to investigate any possible differences in specificity for different glucosinolate substrates among the GTR1 and GTR2 homologs of “A” subgenome, which constitutes half of the genome of two globally important oilseed crops, B. juncea (AABB) and B. napus (AACC).…”
Section: Resultsmentioning
confidence: 99%
“…"*", "**" and "***" denote p values less than 0.05, 0.01 and 0.001, respectively. Mean glucosinolate levels in different tissue types of the transgenic events are provided in supplementary Table S8, S9, S10 and S11, and statistical details are presented in supplementary Table S12 and S13 prerequisite, a novel cotton cell suspension transport assay system was established (Nambiar et al, 2020) and used to test the Brassica GTRs. Using the CCL-1 system, it was shown that all "A" subgenome GTR1 and GTR2 transporters were functional, displaying Km values for all the tested glucosinolates in the micromolar ranges and their transport activity conforming to the Michaelis-Menten kinetics (Figure 2 and Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations